EFFECTIVENESS OF MICRO BUSINESS CREDIT DISTRIBUTION AT PT. PEGADAIAN (PERSERO) PAREPARE CITY BRANCH - Rosdiana; M, A.Pananrangi; Sugianto (P3M Stia Al Gazali Barru and Meraja media, 2022)
[Full Paper] to pdf Copyright (c) 2022 Meraja journal